Aromaterapi Lavender Menurunkan Keluhan Insomnia Pada Lansia - Betty Mufarrohatul Amanah; Dian Ika Puspitasari; Emdat Suprayitno; Zakiyah Yasin; Dian Permatasari (Fakultas Ilmu Kesehatan, 2022)
Aging is an advanced stage of human life. One of the effects experienced by the elderly is sleep disturbances, including insomnia. This study aims to analyze the effect of lavender aromatherapy in reducing insomnia complaints in the elderly. The design of this study used a pre-experiment with one group pretest-posttest. The population of this study was elderly with insomnia in the village of Lembana, Nyalabu Laok village, Pamekasan district, as many as 39 elderly with a sample of 36 elderly with simple random sampling. They were collecting data using the lavender aromatherapy observation technique KSPBJIRS. The study results before receiving lavender essential oil therapy showed that the majority (83%) of the elderly suffered from severe insomnia. Moreover, most (89%) of the elderly, after being treated with lavender essential oil, experienced moderate insomnia. The results of data analysis with paired t-tests obtained a value of = 0.017. Steam with lavender essential oil has the effect of reducing insomnia symptoms in the elderly. Older people with insomnia can be inhaled lavender essential oil.